2011
DOI: 10.1051/epjap/2011110165
|View full text |Cite
|
Sign up to set email alerts
|

LIF spectroscopy of OH radicals in a micro-flow DC discharge in Ar and He with a liquid electrode

Abstract: Abstract. The laser induced fluorescence spectroscopy on a micro-flow discharge with water electrode is carried out in order to investigate OH radicals. The transitions P2(6), P1(4) and P2(3) branches of X 2 Π , ν =0 -A 2 Σ, ν =1 transition are used. Laser-induced fluorescence is used in order to estimate density of OH radicals and density of water vapor in a core of the plasma. Sputtering yield of H2O from the liquid electrode is calculated based on experimental data. It is revealed that plasma core consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…[1,3] There are only few studies concerning the understanding of phenomena occurring in direct current (dc) APGD generated between Ar or He microjets and liquid cathodes. [5,6,[14][15][16][17][18][19] Unfortunately, cited works are rather incomprehensive because do not focus on the dischargeliquid interaction and either do not try to find relationships between concentrations of reactive species in liquid and gas phases of mentioned microdischarges and their spectroscopic parameters under different experimental conditions. Accordingly, APGD generated in the atmosphere of the ambient air between a miniature flow Ar jet and a bulky static liquid cathode (a NaCl solution) has been reported by Shirai et al [14,15] These authors studied the emission characteristic of the microdischarge as a function of the discharge current and the temperature of a NaCl solution used as the liquid cathode, which both were found to be critical for discharge-liquid interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3] There are only few studies concerning the understanding of phenomena occurring in direct current (dc) APGD generated between Ar or He microjets and liquid cathodes. [5,6,[14][15][16][17][18][19] Unfortunately, cited works are rather incomprehensive because do not focus on the dischargeliquid interaction and either do not try to find relationships between concentrations of reactive species in liquid and gas phases of mentioned microdischarges and their spectroscopic parameters under different experimental conditions. Accordingly, APGD generated in the atmosphere of the ambient air between a miniature flow Ar jet and a bulky static liquid cathode (a NaCl solution) has been reported by Shirai et al [14,15] These authors studied the emission characteristic of the microdischarge as a function of the discharge current and the temperature of a NaCl solution used as the liquid cathode, which both were found to be critical for discharge-liquid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies devoted to microdischarges generated between microjets and liquids were mostly undertaken to characterize resulting electrochemical products of discharge reactions, e.g., nanoparticles, nanomaterials, as well as electrical parameters of these discharges under different conditions . There are only few studies concerning the understanding of phenomena occurring in direct current (dc) APGD generated between Ar or He microjets and liquid cathodes . Unfortunately, cited works are rather incomprehensive because do not focus on the discharge–liquid interaction and either do not try to find relationships between concentrations of reactive species in liquid and gas phases of mentioned microdischarges and their spectroscopic parameters under different experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…•OH formation and dynamics on the water surface were also evaluated in the discharge plasma process [111,[122][123][124]. Kanazawa et al [111] studied •OH formation on the liquid surface in the pulsed discharge plasma process by LIF and found that some gaseous •OH could migrate and dissolve into the water.…”
Section: •Oh Measurementmentioning
confidence: 99%
“…The emission spectra show usually the radiation bands of excited states of N 2 , OH and NO and lines of atomic H and O at discharge in nitrogen containing gases [4][5][6]. As far as the discharges in contact with water are concerned, there are some studies where the OH radical concentrations in the ground state were measured in a gas phase for the atmospheric pressure DC discharge in an ambient air, He, Ar and N 2 by a LIF method [6,7] and applying the absorption in UV region for Ar/H 2 O [8]. For nitrogen, it was discovered that OH concentration was about (2-2.3) 9 10 15 cm -3 in the current range of 15-30 mA.…”
Section: Introductionmentioning
confidence: 99%